Quantitative and fiber-selective evaluation of pain and sensory dysfunction in patients with Parkinson's disease. Issue 4 (April 2015) - Chen, Yi; Mao, Cheng-Jie; Li, Si-Jiao; Wang, Fen; Chen, Jing; Zhang, Hui-Jun; Li, Ling; Guo, Sha-Sha; Yang, Ya-Ping; Liu, Chun-Feng
Abstract: Introduction: Pain and sensory disturbances affect many patients with Parkinson's disease (PD). The present study aimed to evaluate the pain and sensory sensitivity of each class of afferent fibers in PD patients and determine the effects of dopaminergic therapy on pain and sensory sensitivity. Methods: Current perception threshold (CPT) and pain tolerance thresholds (PTT) at three frequencies, 2000 Hz, 250 Hz, and 5 Hz, to stimulate Aβ fibers, Aδ fibers, and small C-polymodal fibers, respectively, were measured in 72 PD patients and 35 healthy controls. Results: CPT was higher at all three frequencies and PTT was lower at 2000 Hz and 250 Hz in PD patients with pain versus healthy controls ( P  < 0.05). CPT was higher at 2000 Hz and 250 Hz and PTT was lower at 2000 Hz and 250 Hz in PD patients without pain versus healthy controls ( P  < 0.05). PD patients with pain exhibited higher CPT at 5 Hz and 250 Hz than PD patients without pain ( P  < 0.05). Dopaminergic therapy did not affect CPT or PPT in PD patients ( P  > 0.05). Conclusions: Abnormal Aδ fiber- and Aβ fiber-dependent sensory inputs may exist in PD. Abnormal sensory inputs via C fibers and Aδ fibers might be associated with the presence of pain in PD. Because dopaminergic therapy failed to mitigate these sensory and pain dysfunctions, mechanisms not involving the dopaminergic pathway are likely to be implicated. Highlights: We evaluate sensory sensitivity of each class of afferent fibers in PD patients. Abnormal Aδ fiber- and Aβ fiber-dependent sensory inputs may exist in PD. Abnormal sensory inputs via C and Aδ fibers may be associated with pain in PD. Dopaminergic therapy failed to mitigate these sensory and pain dysfunctions. Peripheral nerve fiber abnormalities play a role in the pain pathogenesis of PD.